Implementasi Islam dalam Pendidikan Karakter di Sekolah Dasar - Frida Febriyani; Fasha Putri Audina; Tika Yulia Damayanti; Yunita Ul Jannah; Hisny Fajrussalam (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Educational institutions are said to be advanced if they are successful in both academic and non-academic fields. Success in this non-academic field includes the attitudes and behavior of students who are good and have noble character. Awareness of how important character education is for the next generation of this nation is growing and putting hope in its development in the field of education. The purpose of this research is of course to find out and be able to implement more about character education from an Islamic perspective. By using qualitative research methods, the researchers obtained results regarding the Islamic perspective in character education and its implementation at the elementary school level. The researchers obtained the results from the questionnaire and then processed the data through descriptive-qualitative analysis. By understanding the various opinions the researchers succeeded in getting the results of the Implementation of Islam in Character Education in Elementary Schools.